Development of Guided Inquiry Oriented with Chemical Representations e-Worksheets to Train Science Process Skills on Chemical Equilibrium - Putri, Robertha Febriana; Novita, Dian (Hydrogen: Jurnal Kependidikan Kimia, 2024)
Chemistry learning, namely chemical equilibrium material, is considered less easy to understand for students because they are less able to represent mutiples of chemical representations, and science process skills are low. This problem was found referring to the results of a pre-research questionnaire of students and interviews with high school teachers in Surabaya. Overcoming this, learning media that helps students understand the material according to the characteristics of students is needed. The purpose of this research is to produce a product in the form of Student worksheet electronic that is feasible to develop on chemical equilibrium material. The method used is research and development with the 4D model which consists of defining, designing, developing, and disseminating stages. This research was only conducted up to the development stage. Student worksheet electronic on chemical equilibrium material was tested on students of class XI-5 SMA Negeri 3 Surabaya who had studied chemical equilibrium material was the subject of this study. This research instrument is in the form of a review sheet, validation sheet, student response questionnaire sheet, observation sheet, test sheet. This research produces guided inquiry Student worksheet electronic media oriented to multiple chemical representations on chemical equilibrium material. The results of Student worksheet electronic validation from the aspects of content validity and construct validity, each obtained a mode of 4 so that it is very valid to use. The results of the student response questionnaire reached an average of 88.3% positive response with a very practical category. The results of pretest and posttest data analysis obtained an increase in science process skills as much as 80% of students get a high criteria n-gain score. It is concluded that the guided inquiry Student worksheet electronic oriented to multiple chemical representations on chemical equilibrium material is feasible to use to train students’ science process skills.